Faecal carriage of multidrug-resistant bacteria and associated risk factors: results from a point prevalence study. (29th August 2022) - Grohs, Patrick; Vilfaillot, Aurélie; Zahar, Jean Ralph; Barbut, Frédéric; Frange, Pierre; Casetta, Anne; Moulin, Véronique; Lawrence, Christine; Baune, Patricia; Bourgeois, Cléo; Bouffier, Axel; Laussucq, Claudine; et al.
Abstract: Objectives: Since 2003, incidences of carbapenemase-producing Gram-negative bacilli (CP-GNB) and vancomycin-resistant Enterococcus faecium (VRE) have steadily increased in France. We therefore conducted a point prevalence study to estimate carriage rates of CP-GNB, VRE and ESBL-producing Enterobacterales (ESBL-PE) and associated risk factors. Methods: Between September 2019 and January 2020, all inpatients hospitalized on a given day in 11 teaching hospitals in the Paris urban area were eligible. Patient interviews and rectal swab screening results were recorded by dedicated nurses. The swabs were plated onto selective chromogenic media and processed using the GeneXpert ® system. Results: Of 2396 patients, 364 (15.2%) yielded at least one multiresistant bacterial isolate, including 29 CP-GNB carriers (1.2%), 13 VRE carriers (0.5%) and 338 ESBL-PE carriers (14%). In 15 patients (4.4% of ESBL-PE carriers and 36.6% of CP-GNB/VRE carriers), concomitant CP-GNB/VRE and ESBL-PE carriage was observed. In 7/29 CP-GNB and 7/13 VRE carriers, carbapenemase production and vanA in the screening samples was only detected with Xpert ® tests. The OXA-48 gene was predominant in 13/34 CP-GNB isolates from 29 carriers. From the 338 ESBL-PE carriers, 372 isolates were recovered, mainly Escherichia coli (61.2%). Among 379 children, 1.1% carried a CP-GNB/VRE strain, and 12.4% carried an ESBL strain. Previous hospitalization outside mainland France, previous antimicrobial treatment and previous ESBL-PE carriage were the main risk factors associated with CP-GNB and/or VRE carriage. Conclusions: The low CP-GNB and VRE prevalence likely reflects the French policy to limit intrahospital spread of CP-GNB and VRE strains.